2020
DOI: 10.3389/fpls.2020.00099
|View full text |Cite
|
Sign up to set email alerts
|

Forest-Scale Phenotyping: Productivity Characterisation Through Machine Learning

Abstract: Advances in remote sensing combined with the emergence of sophisticated methods for large-scale data analytics from the field of data science provide new methods to model complex interactions in biological systems. Using a data-driven philosophy, insights from experts are used to corroborate the results generated through analytical models instead of leading the model design. Following such an approach, this study outlines the development and implementation of a whole-of-forest phenotyping system that incorpora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Our study represents one of the first applications of remote sensing in a quantitative genetic framework for forest trees, particularly tree architectural traits. Previous applications of remote sensing in a genetic framework have studied provenance differences in heat-sum requirements when grown in a common garden environment [34], and highlighted the use of LiDAR technology for whole forest phenotyping following an area-based approach [35].…”
Section: Discussionmentioning
confidence: 99%
“…Our study represents one of the first applications of remote sensing in a quantitative genetic framework for forest trees, particularly tree architectural traits. Previous applications of remote sensing in a genetic framework have studied provenance differences in heat-sum requirements when grown in a common garden environment [34], and highlighted the use of LiDAR technology for whole forest phenotyping following an area-based approach [35].…”
Section: Discussionmentioning
confidence: 99%
“…The use of thermal imagery provides an efficient means of phenotyping this variation in gs, and, for instance, canopy temperature was used to provisionally identify droughttolerant black poplar genotypes within a genetics trial comprising 503 genotypes [25]. Further research should utilise thermal imagery to identify drought-tolerant radiata pine genotypes within genetic trials and from well-characterised plantations using landscapelevel phenotyping methods [53,54]. The identification of these genotypes will allow growers to match genotypes to drought-prone sites to optimise growth and mitigate the impacts of climate change in more arid growing regions.…”
Section: Discussionmentioning
confidence: 99%
“…Bombrun used a machine learning approach to screen indicators that have a strong influence on forest productivity from multiple observations of forests. The results revealed that topology is one of the important drivers of forest productivity [18]. However, the study did not go further in exploring which specific topological indicators influenced forest productivity.…”
Section: Introductionmentioning
confidence: 88%